2020
DOI: 10.1186/s12913-020-05814-1
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of hypertonic saline inhalations for infant bronchiolitis

Abstract: Background Pharmacological treatment for bronchiolitis is primarily supportive because bronchodilators, steroids, and antibiotics, show little benefit. Clinical studies have suggested that nebulized 3% hypertonic solution is useful for infants with bronchiolitis. This study aims to evaluate the cost-effectiveness of the HS inhalations in infant bronchiolitis in a tropical country. Methods Decision tree analysis was used to calculate the expected costs and QALYs. All cost and use of resources were collected d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Previous publications have shown that bronchiolitis has a relevant impact on healthcare resources consumption and related expenditures, especially in severe cases, and any intervention that reduces the burden of disease and costs is highly appropriate to any health system [ 3 , 4 , 9 , 17 ]. Surfactant is the therapy with the highest level of expectations due to a positive effect in PICU length of stay, but still a few evidence in endpoints such as mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications have shown that bronchiolitis has a relevant impact on healthcare resources consumption and related expenditures, especially in severe cases, and any intervention that reduces the burden of disease and costs is highly appropriate to any health system [ 3 , 4 , 9 , 17 ]. Surfactant is the therapy with the highest level of expectations due to a positive effect in PICU length of stay, but still a few evidence in endpoints such as mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold (US$ 257) can be used as a reference for the control and regulation of prices in the country. Show evidence related to the economic impact this drug is essential to policy makers and physician [ 21 ] especially in developing countries where economic evaluation of drugs and medical devices in pediatric patients are increasing [ 17 , 22 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Available data show that the ICU management of bronchiolitis, despite being expensive in absolute terms, consists of interventions that are likely to be cost-effective. 50 , 51 , 68 , 69 , 70 , 71 , 72 , 73 , 74 Data are summarised in Table 1 : this is not a formal cost-effectiveness analysis, since it is difficult to precisely assess some of these effects (e.g. the cost of inter-hospital transfer or the effects on families, which may vary according to several factors) and studies have different designs and outcomes.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…2,3 Mortalitas anak bronkiolitis berkisar antara 0,2-7%. 4 Sebagian besar panduan bronkiolitis merekomendasikan terapi suportif berupa suplementasi oksigen, hidrasi adekuat, dan pemberian ventilasi mekanik bila diperlukan. Terapi lain seperti steroid, salbutamol, dan salin hipertonik sering digunakan dalam terapi bronkiolitis tetapi efektivitasnya masih kontroversial.…”
unclassified